Deskripsi Masjid Alit Ki Ageng Gribig dan Dakwah Kultural Awal di Klaten Jawa Tengah - Retno Kartini Savitaningrum (Jurnal Lektur Keagamaan, 2015)
Masjid Alit Ki Ageng Gribig (Ki Ageng Gribig’ Small Mosque) is the oldest mosque in Jatinom subdistrict of Klaten (Central Java). This mosque was built by Ki Ageng Gribig in the 17th century, or during the reign of Sultan Agung Hanyakrakusuma (1613-1645 M). However, the story of establishment might not be properly known because there are no any records as well as inscriptions stating the detail of the establishment. It is mentioned in an inscription around the mosque saying that the restoration carried out in 1862 M. Many people believe that the mosque was founded by Ki Ageng Gribig known as Sheikh WasibagnoTimur during his youth ages. He played a major role in the spread of Islam in Klaten area of Central Java. The spread of Islam in the community was centered on this mosque. In addition, Ki Ageng Gribig established Islam as the religion that accommodates local culture which was called as Yakowiyu tradition or simply distributing apem (aJavanese meal) which is still celebrated by the community Jatinom annually in Islamic month of Safar. The two such kinds of Islamic ceremonies were performed as a means for propagating Islam to the local people of Jatinom. Although in later years, the bigger mosque than that mosque was built namely the Masjid Ageng Jatinom, the Masjid Alit Ki Ageng Gribig still maintains its existence. Besides, the mosque plays an important role in preserving the people traditions of the past, namely Yaqowiyu traditions within the process ofda’wah since its early days of development until the present. This is an urgent need to preserve the heritage of the great ulama whether in the form of building artifacts and cultural artifacts.